Valuasi ekonomi Setu Pedongkelan, Kota Depok, Jawa Barat (pemanfaatan sumber daya perikanan) - Gusti Ayu Dwi Wulandari (e-Jurnal Ekonomi Sumberdaya dan Lingkungan, 2021)
This study aims to identify the types of utilization found in Setu Pedongkelan and estimate the economic value of Setu Pedongkelan through fisheries utilization. The use of fisheries in Setu Pedongkelan is capture fisheries. The data used in this research are primary data in the form of survey results, interviews and online questionnaires as well as secondary data obtained from the documentation archive. The method used in this research is the market price method. The results of the study found that the types of utilization found in Setu Pedongkelan include direct use such as fisheries, irrigation and recreation. In addition, there are also indirect uses such as places for biota to find food, flood control, spawning, conservation and places or research facilities. This research also gives the result that the economic value of Setu Pedongkelan from fisheries utilization is IDR 2,472,960,000.